EMBROIDERY AND SUBJECTIVITY: EMBROIDERY AS A CARTOGRAPHIC GESTURE (Palíndromo, 2019)
This article intends to argue about the relations between the poetic and processual manufacture of embroidery and the problem of the subjectivity, perceiving embroidery as a cartographic gesture, as suggested by poststructuralist authors such as Deleuze and Guattari, and also Rolnik. For such purpose, the poetic processes experienced in the making of a work of a final term paper named Os avessos de nós: bordado na representação do corpo feminino (The reverse of us: embroidery in the representation of the female body), are reviewed and analyzed. This work relates the concepts around subjectivity, in specific the female subjectivity, with the processes of manufacturing embroidery, focusing in what are the contaminations between the manual work and the representation of the body as a sensitive territory. Thus, it is intended to comprehend in what ways does the practice relates with the body, the represented one and also the body of the agent, and how does it function as a way of materializing developments, and also, the importance of the use of the called crafts in the maintenance of subjectivity.
Keywords: embroidery; subjectivity; cartography; body; becoming